Synthesis, characterization and thermal behaviour of solid alkali metal mandelates in pyrolytic and oxidant atmosphere - Silva, R. C. [UNESP]; Caires, F. J. [UNESP]; Gomes, D. J. C.; Colman, T. A. D. [UNESP]; Ionashiro, M. [UNESP] (Elsevier B.V., 2016)
Characterization, thermal stability and thermal decomposition of alkali metal mandelates, M(C6H5CH(OH)CO2)nH(2)O (where M represents Na, K, Rb and Cs and n = 0.3 (Na), 0.6 (K), 2 (Rb) and 1 (Cs)) were investigated employing simultaneous thermogravimetry and differential scanning calorimetry (TG-DSC), atomic absorption spectrophotometry (AA), X-ray diffractometry and TG-DSC coupled to infrared spectrophotometer (FTIR). For all the compounds, the mass loss occurs in the beginning of the TG-DSC curves. In the nitrogen atmosphere it was observed that the mass loss of the anhydrous compounds occurs in four or five steps and the mass loss is still observed up to 1000 degrees C, except for the anhydrous compounds under dynamic dry air atmosphere, after the first three steps occurs with the formation of the respective carbonate. The results also provided information concerning the thermal stability and decomposition as well as identification of the gaseous products evolved during the thermal decomposition of these compounds. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Alkali metals; Mandelate; Thermal behaviour; TG-DSC coupled to FTIR